The diagnosis, treatment and outcomes following the management of giant radicular cyst of the maxilla: Diagnosis, pengobatan dan hasil setelah penatalaksanaan kista radikuler raksasa pada rahang atas - M. Riza Firdaus; Moh Gazali Malik (Makassar Dental Journal PDGI Makassar, 2026)
Radicular cysts are the most common odontogenic cysts originating from inflammation. These cysts are almost always associated with pulp necrosis, which causes inflammation of the periapical tissue, although they usually do not show symptoms unless infected. This study examined the diagnosis, treatment, and outcomes following management of giant radicular cysts in the maxilla based on articles indexed in four databases, namely PubMed-Medline, Embase, Scopus, and Google Scholar, from 2014 to 2024. The initial search yielded 38 articles, but only 9 articles met the eligibility criteria. In addition to clinical examination, further radiographic examination is also necessary to plan treatment. Treatment options depend on factors such as the extent of the lesion, its relationship to surrounding structures, the clinical characteristics of the lesion, and the patient's systemic condition. It is concluded that it is very important for dentists to de-termine the correct diagnosis and treatment plan in order to provide optimal care.